STRATEGI IMPLEMENTASI PROGRAM PERLUASAN KEPESERTAAN BPJS KESEHATAN DI KABUPATEN KUBU RAYA PROVINSI KALIMANTAN BARAT - Sri Maryuni; Pardi Pardi; Agus Eka (Jurnal Administrasi Publik dan Pembanguan, 2019)
This research examines  strategy for implementing the expansion program of participation of BPJS (Social Security Organizing Agency) Health in Kubu Raya Regency because there is data and evidence show that the target of membership of the BPJS Health has not yet been determined. The purpose of this research is to seek out appropriate strategies that to achieve the target of BPJS Health participation in 2019. This research uses a qualitative descriptive research method since researchers want to understand the factors that influence on the low achievement of the participation of BPJS Health in Kubu Raya Regency West Kalimantan Province.  The result from the research conducted showed that there are some factors bring to the low achievement of BPJS Health participation targets in Kubu Raya Regency, they are lack of public knowledge about BPJS Health, lack of socialization about the benefits and importance of BPJS Health participation, and lack of involvement of the Kubu Raya Regional Government in supporting the success of the JKN-KIS program. The researchers recommend a strategy in overcoming this issue is to optimise the socialisation intensely to the public related to the Health BPJS, collaboration with the Regional Government and associated institutions in expanding the membership of BPJS Health.